The impact of combined age-related vision loss and dementia on the participation of older adults: A scoping review. - Colleen McGrath; Inaara Karsan; Ann Marie Corrado; Taylor Ashley Lyons; Melanie Blue (PLoS ONE)
Introduction There are a growing number of older adults with combined age-related vision loss (ARVL) and dementia. Existing literature shows the pervasive impact that both diagnoses have separately on the participation of older adults, however, little is known about the societal participation of older adults with both conditions. As such, the aim of this scoping review was to explore the combined impact of ARVL and dementia on the participation of older adults, with a specific focus on highlighting strategies that help mitigate the impact of ARVL and dementia on participation. Methods This study utilized a scoping review, informed by the framework by Arksey and O'Malley [1]. Two researchers independently ran a total of 62 search terms across four categories in six databases (PubMed, CINAHL, Scopus, Embase, Medline, PsycINFO), with an initial yield of 2,053 articles. Grey literature was also included in this scoping review and was retrieved from organizational websites, brochures, conference proceedings, and a Google Scholar search. The application of study inclusion criteria resulted in a final yield of 13 empirical studies and 10 grey literature sources. Results Following detailed thematic analysis of the empirical and grey literature sources, four themes emerged regarding the impact of combined ARVL and dementia on the participation of older adults including: 1) Managing the pragmatic aspects of a dual diagnosis; 2) Diverse approaches to risk assessment and management; 3) Adopting a multi-disciplinary approach to facilitate care and; 4) Using compensatory strategies to facilitate participation. Conclusions The four themes highlight the challenges older adults with these combined diagnoses experience, which limit their opportunities for meaningful participation. Given the scarcity of research on this topic, future research should identify the type of ARVL and dementia diagnoses of study participants, conduct qualitative research about the lived experiences of older adults with a dual diagnosis, and broaden the geographic scope of research.